The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/om049575l
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Stabilized Silyl Cations. 8. Carbon−Carbon Bond Formation through a Novel Interchelate Molecular Rearrangement in Pentacoordinate Siliconium-Ion Salts1

Abstract: Tricyclic neutral pentacoordinate silicon complexes are formed by a novel intramolecular rearrangement of pentacoordinate bis(imino nitrogen)-chelated siliconium halide salts. The rearrangement consists of an interchelate aldol-type condensation of imine moieties, forming a new carbon-carbon bond and a third chelate ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…It was shown that the ability of group 14 elements for the coordination expansion [3,5] allows to stabilize organometallic cations by the introduction of R 2 N or RO groups into hydrocarbyl substituents at the M atom. The stabilization of cations arises from the intramolecular interaction between the lone electron pair(s) of the nitrogen or oxygen atoms with the formally empty p-orbital of the central cation atom M (M = Si, Ge) [6][7][8][9]. Recently, it was shown that the germyl cation [PhGe(OCH 2 CH 2 NMe 2 ) 2 ] + can be stabilized by the electronic effects of the b-dimethylaminoethoxy group [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the ability of group 14 elements for the coordination expansion [3,5] allows to stabilize organometallic cations by the introduction of R 2 N or RO groups into hydrocarbyl substituents at the M atom. The stabilization of cations arises from the intramolecular interaction between the lone electron pair(s) of the nitrogen or oxygen atoms with the formally empty p-orbital of the central cation atom M (M = Si, Ge) [6][7][8][9]. Recently, it was shown that the germyl cation [PhGe(OCH 2 CH 2 NMe 2 ) 2 ] + can be stabilized by the electronic effects of the b-dimethylaminoethoxy group [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of Cyanotrimethylsilane with Methylsiliconium Chloride (2a). 2a was prepared by the reaction of methyltrichlorosilane and the O- (trimethylsilyl)hydrazide derivative ( 8 ) as described previously and shown in eq 4 …”
Section: Resultsmentioning
confidence: 99%
“…Complexes 1 readily dissociate to ionic siliconium halide salts ( 2 ) at ambient temperature in chloroform solutions (eq 1) . The ionic 2 was shown to undergo an interchelate molecular rearrangement, consisting of an internal aldol-type condensation, presumably catalyzed by its own halide counterion (eq 2) . Surprisingly, the hexacoordinate silacyclobutane complexes ( 4 ) also undergo this rearrangement, in the absence of counterion, forming 5 (eq 3).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse silicon chemicals that have organic carbon scaffolds around the silicon atom (i.e., where silicon is acting as a heteroatom, not a scaffold element) are also known, although many react very rapidly with water. Examples of such chemicals include zwitterionic silicon compounds [49]; a range of organosilicon molecules with negatively charged silicon centers [50][51][52]; positively charged silicium (tricoordinate silicon [53]); and pentacoordinate silicons [54,55], some of which have silicon bonded to five different atoms at once [23], that can have useful catalytic properties in carbon-carbon bond formation [56].…”
Section: Observed Functional Diversity Of Silicon Chemistrymentioning
confidence: 99%